Semiotic Analysis of the Film Black God, White Devil (1964), directed by Glauber Rocha - Valverde da Silva, Ana Luiza; Escribá Maroto, Almudena (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2015)
In 1964, Glauber Rocha wrote and directed a movie “Black God, White Devil”. It was in the same year that Brazil suffered military coup. At that time, talks about politics or social problems were a messy affair due to the strong threat of repression. This film communicates the dichotomy between good and evil, cultured and uncultured, order and disorder, social differences, the symbolic constructions of space as semiosfera, the borders and chaos. For the director, religion is closely related to politics. It is stated the desire for power between the political-social (interest of landowners on workers) and religious (interest of preachers over believers). This analysis runs on such symbolic dualities, paying attention to the semiotic discussion by theorists such as Yuri Lotman, Michael Foucault, Mijaíl Bajtín, Umberto Eco, among others. The article intention is to examine how Glauber Rocha constructed the symbolic spaces along its film, and to understand the critical message that he provides.